The burden of skin and subcutaneous diseases: findings from the global burden of disease study 2019 - Yakupu, Aobuliaximu; Aimaier, Rehanguli; Yuan, Bo; Chen, Bin; Cheng, Jia; Zhao, Yaohua; Peng, Yinbo; Dong, Jiaoyun; Lu, Shuliang (Frontiers in Public Health, 2023)
Background The small number of existing integrative studies on the global distribution and burden of all types of skin and subcutaneous diseases hinders relevant comparisons. Objective This study aimed to determine the latest distribution, epidemiological differences, and factors potentially influencing each skin and subcutaneous disease and the policy implications. Methods Data on the skin and subcutaneous diseases were obtained from the Global Burden of Disease Study 2019. The incidence, disability-adjusted life years (DALYs), and deaths due to skin and subcutaneous diseases in 204 countries and regions from 1990 to 2019 were analyzed and stratified by sex, age, geographical location, and sociodemographic index (SDI). The annual age-standardized rate of change in the incidence was obtained to evaluate temporal trends. Results Of 4,859,267,654 (95% uncertainty interval [UI], 4,680,693,440–5,060,498,767) new skin and subcutaneous disease cases that were identified, most were fungal (34.0%) and bacterial (23.0%) skin diseases, which accounted for 98,522 (95% UI 75,116–123,949) deaths. The burden of skin and subcutaneous diseases measured in DALYs was 42,883,695.48 (95%UI, 28,626,691.71-63,438,210.22) in 2019, 5.26% of which were years of life lost, and 94.74% of which were years lived with disability. The highest number of new cases and deaths from skin and subcutaneous diseases was in South Asia. Globally, most new cases were in the 0–4-year age group, with skin and subcutaneous disease incidence slightly higher in men than in women. Conclusion Fungal infections are major contributors to skin and subcutaneous diseases worldwide. Low–middle SDI states had the highest burden of skin and subcutaneous diseases, and this burden has increased globally. Targeted and effective management strategies based on the distribution characteristics of each country are, thus, required to reduce the burden of skin and subcutaneous diseases.